2021
DOI: 10.1055/a-1341-0788
|View full text |Cite
|
Sign up to set email alerts
|

EUS-guided gastroenterostomy versus enteral stenting for gastric outlet obstruction: Systematic review and meta-analysis

Abstract: Abtract Background and study aims Endoscopic and surgical techniques have been utilized for palliation of gastric outlet obstruction (GOO). Enteral stenting (ES) is an established technique with high clinical success and low morbidity rate. Endoscopic ultrasound-guided gastroenterostomy (EUS-GE) is a novel approach that aims to provide sustained palliation of GOO. We conducted a comprehensive review and meta-analysis to evaluate the effectiveness in terms of clinical and technical success, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…A 2021 metaanalysis of 5 studies assessing 659 patients reported a pooled overall AE rate of 10.7% with EUS-GE, with a major AE rate of 3.7%. 101 A 2020 meta-analysis of 12 studies assessing 285 patients reported a similar pooled overall AE rate of 12%. 102 The most common associated AE is stent maldeployment into the peritoneum resulting in perforation, occurring in up to 6.8% to 10% of procedures.…”
Section: Eus-ge and Enteroenterostomymentioning
confidence: 96%
“…A 2021 metaanalysis of 5 studies assessing 659 patients reported a pooled overall AE rate of 10.7% with EUS-GE, with a major AE rate of 3.7%. 101 A 2020 meta-analysis of 12 studies assessing 285 patients reported a similar pooled overall AE rate of 12%. 102 The most common associated AE is stent maldeployment into the peritoneum resulting in perforation, occurring in up to 6.8% to 10% of procedures.…”
Section: Eus-ge and Enteroenterostomymentioning
confidence: 96%
“…When compared to transluminal SEMS placement, EUS-GE have comparable technical and clinical effectiveness. Chandan et al [ 109 ] reported a pooled rate for technical and clinical success of 95.2% and 93.3% in EUS-GE and 96.9% and 85.6% in SEMS. Pooled rate of reintervention was significantly lower with EUS-GE compared to SEMS (4% vs. 23.6%, p = 0.001); however, AEs were comparable between the two techniques.…”
Section: Lumen-apposing Metal Stents (Lams)mentioning
confidence: 99%
“…Studies have demonstrated the feasibility of this technique with high success rates and few adverse events (AEs), as well as long-term durability and a low rate of reintervention 12 15 16 17 18 . Additional studies have found comparable efficacy and safety to endoscopic stenting but with fewer recurrences requiring reintervention 19 20 .…”
Section: Introductionmentioning
confidence: 99%